PENGARUH TEMAN SEBAYA TERHADAP PERILAKU KONSUMSI PADA SISWA KELAS 12 SMK LAB BUSINESS SCHOOL TANGERANG - Nurdiana, Nurdiana (Journal of Business Education and Social, 2023)
The aim of this research is to determine whether or not there is peer influence on consumption behavior. This study uses a quantitative approach. The subjects of this research were 35 class XII students at SMKS Lab Business School Tangerang. The data collection method used was a questionnaire. The results of this research show the influence of peers on consumption behavior. Peers have a positive influence on consumption behavior, the more conducive the influence of the peer group, the more rational the consumption behavior, and the more peers there are, the higher the influence on students' consumption behavior..